2016
DOI: 10.15252/embr.201540882
|View full text |Cite
|
Sign up to set email alerts
|

GemC1 controls multiciliogenesis in the airway epithelium

Abstract: Multiciliated cells are terminally differentiated, post-mitotic cells that form hundreds of motile cilia on their apical surface. Defects in multiciliated cells lead to disease, including mucociliary clearance disorders that result from ciliated cell disfunction in airways. The pathway controlling multiciliogenesis, however, remains poorly characterized. We showed that GemC1, previously implicated in cell cycle control, is a central regulator of ciliogenesis. GemC1 is specifically expressed in ciliated epithel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
127
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 81 publications
(134 citation statements)
references
References 53 publications
7
127
0
Order By: Relevance
“…Two related coiled-coil proteins, Multicilin and Gemc1, are both necessary and sufficient to initiate MCC differentiation, acting as co-regulators in a transcriptional complex with a subset of the E2F proteins (Arbi et al, 2016;Kyrousi et al, 2015;Ma et al, 2014;Stubbs et al, 2012;Terre et al, 2016;Zhou et al, 2015). The complex between Multicilin, E2f4 and DP1 (EDM) in particular appears to directly activate gene expression required for centriolar biogenesis (Ma et al, 2014), thus driving a novel form of organelle assembly that enables MCCs to form the hundreds of basal bodies required for multiple ciliation.…”
Section: Introductionmentioning
confidence: 99%
“…Two related coiled-coil proteins, Multicilin and Gemc1, are both necessary and sufficient to initiate MCC differentiation, acting as co-regulators in a transcriptional complex with a subset of the E2F proteins (Arbi et al, 2016;Kyrousi et al, 2015;Ma et al, 2014;Stubbs et al, 2012;Terre et al, 2016;Zhou et al, 2015). The complex between Multicilin, E2f4 and DP1 (EDM) in particular appears to directly activate gene expression required for centriolar biogenesis (Ma et al, 2014), thus driving a novel form of organelle assembly that enables MCCs to form the hundreds of basal bodies required for multiple ciliation.…”
Section: Introductionmentioning
confidence: 99%
“…The molecular pathway of GemC1/Lynkeas-Mcidas-c-Myb-Foxj1 is highly conserved on different tissues and among different organisms, as we have shown that GemC1/Lynkeas also participates in the differentiation of multiciliated cells in the mouse airway epithelium, 31 while GemC1/Lynkeas also controls the multiciliation process in zebrafish. 32 Taking into account these results and given the fact that Mcidas is essential for multiciliation process in human airway, 31,33 it is plausible that GemC1/Lynkeas also participates in multicilated cell differentitaion in humans.…”
mentioning
confidence: 89%
“…18 The role of Mcidas and GemC1/Lynkeas in radial glial cells fate commitment decisions was addressed by overexpression and depletion experiments. Mcidas is also able to regulate its own expression 13,31 ( Fig. 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Factors required for multiciliogenesis, including Multicilin (Mcidas)5, GemC1 (refs 6, 7), cyclin O (Ccno)89, and the transcription factors p73 (refs 10, 11) and Foxj1 (refs 12, 13) are upregulated and maintained in a transcriptional network in cells committed to the multiciliated lineage3. How multiciliation is influenced by environmental cues is however incompletely understood.…”
mentioning
confidence: 99%